Do transparent exopolymeric particles (TEP) affect the toxicity of nanoplastics on Chaetoceros neogracile?. (July 2019) - González-Fernández, Carmen; Toullec, Jordan; Lambert, Christophe; Le Goïc, Nelly; Seoane, Marta; Moriceau, Brivaela; Huvet, Arnaud; Berchel, Mathieu; Vincent, Dorothée; Courcot, Lucie; Soudant, Philippe; Paul-Pont, Ika
Abstract: The potential presence of nanoplastics (NP) in aquatic environments represents a growing concern regarding their possible effects on aquatic organisms. The objective of this study was to assess the impact of polystyrene (PS) amino-modified particles (50  nm PSNH2 ) on the cellular and metabolic responses of the diatom Chaetoceros neogracile cultures at two essential phases of the growth cycle, i.e. exponential (division) and stationary (storage) phases. Both cultures were exposed for 4 days to low (0.05 μg mL −1 ) and high (5 μg mL −1 ) concentrations of PS-NH2. Exposure to NP impaired more drastically the major cellular and physiological parameters during exponential phase than during the stationary phase. Only an increase in ROS production was observed at both culture phases following NP exposures. In exponential phase cultures, large decreases in chlorophyll content, esterase activity, cellular growth and photosynthetic efficiency were recorded upon NP exposure, which could have consequences on the diatoms life cycle and higher food-web levels. The observed differential responses to NP exposure according to culture phase could reflect i) the higher concentration of Transparent Exopolymer Particles (TEP) at stationary phase leading to NP aggregation and thus, probably minimizing NP effects, and/or ii) the fact that dividing cells during exponential phase may be intrinsically more sensitive to stress. This work evidenced the importance of algae physiological state for assessing the NP impacts with interactions between NP and TEP being one key factor affecting the fate of NP in algal media and their impact to algal' cells. Graphical abstract: Image 1 Highlights: Interaction of NP and diatoms was studied at exponential and stationary phases. Transparent Exopolymer Particles (TEP) alter NP fate by aggregating NP. NP impairs major physiological traits of diatoms at exponential phase. Whatever the aggregation state, NP promotes oxidative stress at both growth phases. Abstract : The interaction between nanoplastics (NP) and transparent exopolymeric particles is one key factor affecting the fate of NP in algal media and their impact to algal' cells.